2003
DOI: 10.1038/sj.bjc.6600827
|View full text |Cite
|
Sign up to set email alerts
|

Marked inactivation of O6-alkylguanine-DNA alkyltransferase activity with protracted temozolomide schedules

Abstract: Temozolomide, an oral DNA methylator that inactivates the DNA repair enzyme O 6 -alkylguanine-DNA alkyltransferase (AGAT), has demonstrated anticancer activity on protracted schedules. Protracted schedules may lead to an 'autoenhancement' of temozolomide's inherent cytotoxic potential by cumulative reduction of the cell's capacity for AGAT-mediated DNA repair and resistance. This study was undertaken to characterise AGAT inactivation and regeneration in the peripheral blood mononuclear cells (PBMCs) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
212
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(223 citation statements)
references
References 22 publications
4
212
2
4
Order By: Relevance
“…This regimen may yield similar results with respect to efficacy, but a higher rate of toxicity, specifically lymphopenia and infection, have been reported [8,9]. The latter two regimens aim at a dose intensification, which could enhance the direct cytotoxic effect of TMZ and which might deplete the DNA repair enzyme O 6 -methylguanine DNA Hau, 5 methyltransferase (MGMT) [10]. This enzyme modulates resistance to alkylating chemotherapeutic agents [11].…”
Section: Introductionmentioning
confidence: 95%
“…This regimen may yield similar results with respect to efficacy, but a higher rate of toxicity, specifically lymphopenia and infection, have been reported [8,9]. The latter two regimens aim at a dose intensification, which could enhance the direct cytotoxic effect of TMZ and which might deplete the DNA repair enzyme O 6 -methylguanine DNA Hau, 5 methyltransferase (MGMT) [10]. This enzyme modulates resistance to alkylating chemotherapeutic agents [11].…”
Section: Introductionmentioning
confidence: 95%
“…This was somewhat higher than previous values (Middleton et al, 2000b: range 2.2 -25.6, mean 12.6) but similar to other ongoing studies (range 2.3 -51.6, mean 15.5: GPM unpublished results). Another study of adult patients has reported a range of B0.6 to B19 Fm mg À1 DNA and a much lower mean of 6.974.7 Fm mg À1 DNA (Tolcher et al, 2003). Some of these differences may be a consequence of the age or disease status of the study groups.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reporting MGMT in adult PBMCs have also shown a range of extents of depletion by temozolomide. A variety of dose regimen and schedules have been examined but complete depletion of MGMT has been observed in very few patients and very wide variations in depletion are always observed (Lee et al, 1994;Gander et al, 1999;Middleton et al, 2000b;Tolcher et al, 2003). The reasons for this have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protracted administration of temozolomide may lead to a marked and sustained inactivation of MGMT leading to an ''autoenhancement" of temozolomide's inherent cytotoxic potential by cumulative reduction of the leukemic blasts' capacity for MGMT-mediated DNA repair and resistance [20]. MGMT activity can be reduced by approximately 80% in patients treated with this dosing schedule [20]. Thus, we designed an exploratory clinical study to test two hypotheses: (1) Can temozolomide therapy be tailored according the MGMT methylation status in patients with AML?…”
Section: Introductionmentioning
confidence: 99%